The Effect of Good Corporate Governance, Sales Growth, Capital Structure, Liquidity, and Firm Size on Firm Value: Evidence From Indonesian Industrial - Rusti Juliandini, Wiga; Susanti, Nora; Pratama, Indra Mulia (Journal of English Language and Education, 2026)
This study examines the effect of Good Corporate Governance (GCG), sales growth, capital structure, liquidity, and firm size on firm value in industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. A quantitative approach was employed using secondary data obtained from published financial statements. The sample consisted of 20 industrial companies selected through purposive sampling, resulting in 100 panel data observations. Panel data regression analysis was conducted using EViews 12. The findings indicate that capital structure has a positive and significant effect on firm value, while GCG, sales growth, liquidity, and firm size do not show a significant influence. Simultaneously, all independent variables jointly affect firm value. These results suggest that an optimal capital structure plays a crucial role in enhancing firm value by strengthening investor confidence and improving market perceptions. Therefore, managers in industrial sector companies are encouraged to carefully manage their capital structure to maintain financial stability and increase investment attractiveness in the capital market.